Effect of microcracking on the uniaxial tensile response of β-eucryptite ceramics: Experiments and constitutive model. (15th August 2017) - Cooper, R.C.; Bruno, G.; Wheeler, M.R.; Pandey, A.; Watkins, T.R.; Shyam, A.
Abstract: A constitutive model for the nonlinear or "pseudoplastic" mechanical behavior in a linear-elastic solid with thermally induced microcracks is developed and applied to experimental results. The model is termed strain dependent microcrack density approximation ( SDMDA ) and is an extension of the modified differential scheme that describes the slope of the stress-strain curves of microcracked solids. SDMDA allows a continuous variation in the microcrack density with tensile loading. Experimental uniaxial tensile response of β-eucryptite glass and ceramics with controlled levels of microcracking is reported. It is demonstrated that SDMDA can well describe the extent of non-linearity in the experimental uniaxial tensile response of β-eucryptite with varying levels of microcracking. The advantages of the SDMDA are discussed in regard to tensile loading. Graphical abstract: We develop a constitutive equation termed strain dependent microcrack density approximation (SDMDA) that models the uniaxial tensile behavior of β-eucryptite with various levels of microcracking. Model results are compared with experimental results on specimens that were heat treated to produce different levels of microcracking. Image